Early Post-stroke Cognition: In-hospital Predictors and the Association With Functional Outcome - Sharma, Richa; Mallick, Dania; Llinas, Rafael H.; Marsh, Elisabeth B. (Frontiers in Neurology, 2020)
Purpose: To characterize and predict early post-stroke cognitive impairment by describing cognitive changes in stroke patients 4-8 weeks post-infarct, determining the relationship between cognitive ability and functional status at this early time point, and identifying the in-hospital risk factors associated with early dysfunction. Materials and Methods: Data were collected for 214 patients with ischemic stroke and 39 non-stroke controls. Montreal Cognitive Assessment (MoCA) exams were administered at post-hospitalization clinic visits approximately 4-8 weeks after infarct. MoCA scores were compared for patients with: no stroke, minor stroke (NIH Stroke Scale [NIHSS] < 5), and major stroke. Ordinal logistic regression was performed to assess the relationship between MoCA score and functional status (modified Rankin Scale score (mRS)) at follow-up. Predictors of MoCA < 26 and < 19 (cutoffs for mild and severe cognitive impairment respectively) at follow-up were identified by multivariable logistic regression using variables available during hospitalization. Results: Post stroke cognitive impairment was common, with 66.8% of patients scoring < 26 on the MoCA and 22.9% < 19. The average total MoCA score at follow-up was 18.7 (SD 7.0) among major strokes, 23.6 (SD 4.8) among minor strokes, and 27.2 (SD 13.0) among non-strokes (p=<0.0001). The follow-up MoCA score was associated with the follow-up mRS in adjusted analysis (OR 0.69; 95% C.I. 0.59-0.82). Among patients with no prior cognitive impairment (N=201), a lack of pre-stroke employment, admission NIHSS > 6, and left-sided infarct predicted a follow-up MoCA < 26 (c-statistic 0.75); while admission NIHSS > 6 and infarct volume > 17cc predicted a MoCA < 19 (c-statistic 0.75) at follow-up. Conclusion: Many patients experience early post-stroke cognitive dysfunction that significantly impacts function during a critical time period for decision-making regarding return to work and future independence. Dysfunction measured at 4-8 weeks can be predicted during the inpatient hospitalization. These high-risk individuals should be identified for targeted rehabilitation and counseling to improve longer-term post-stroke outcomes.